2015
DOI: 10.1016/j.bjorl.2014.05.034
|View full text |Cite
|
Sign up to set email alerts
|

Auditory and language skills of children using hearing aids

Abstract: The diagnosis of hearing loss and the clinical interventions occurred late, contributing to impairments in auditory and language development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
11

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 19 publications
0
8
0
11
Order By: Relevance
“…Corroborando os achados de um estudo (Boscolo & Santos, 2005) com o objetivo de investigar os sentimentos, reações e expectativas de pais em relação à deficiência auditiva dos filhos, por meio da análise do discurso do sujeito coletivo, evidencia melhora em dois domínios do comportamento auditivo: sociais e de escuta, após a adaptação do AASI. Ainda, em outro estudo (Penna, Lemos & Alves, 2015), os autores não encontraram correlação nas atividades diárias de usuários de AASI, entre a avaliação fonológica e a detecção dos Sons de Ling com o comportamento auditivo.…”
Section: Discussionunclassified
“…Corroborando os achados de um estudo (Boscolo & Santos, 2005) com o objetivo de investigar os sentimentos, reações e expectativas de pais em relação à deficiência auditiva dos filhos, por meio da análise do discurso do sujeito coletivo, evidencia melhora em dois domínios do comportamento auditivo: sociais e de escuta, após a adaptação do AASI. Ainda, em outro estudo (Penna, Lemos & Alves, 2015), os autores não encontraram correlação nas atividades diárias de usuários de AASI, entre a avaliação fonológica e a detecção dos Sons de Ling com o comportamento auditivo.…”
Section: Discussionunclassified
“…It was observed that the characteristics of the children in the intervention groups certainly determined the needs for adaptations to be made (Lederberg, Schick, & Spencer, 2013), with emphasis on the time of sensory deprivation (Bornstein, 2018;Wake & Carew, 2016), the restricted use of hearing aids for some of them (Penna, Lemos, & Alves, 2015;Vasconcelos, & Pereira, 2015) and the late entry into the hearing (re)habilitation program (Bicas, Guijo, Delgado-Pinheiro, 2017;Oliveira, Penna, & Lemos, 2015;Tabaquim et al, 2013), which were factors verified in the sample and which should be considered in the development of strategies for phonological work.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past 30 years, surprising technological and scientific advances have given children with hearing impairment access to speech sounds at a time favorable to their language development (Wake & Carew, 2016;Bornstein, 2018). Even so, due to the variables involved in the (re)habilitation process -such as: age at diagnosis, cause and degree of hearing impairment, time of use of hearing aid devices, family involvement in the therapeutic process (Bicas, Guijo, & Delgado-Pinheiro, 2017;Moret, 2017;Oliveira, Penna, & Lemos, 2015;Penna, Lemos, & Alves, 2015;Tabaquim et al, 2013;Vasconcelos & Pereira, 2015), among other factors -, hearing impaired children have a disadvantage in relation to hearing children in terms of phonological processing and are, therefore, a risk population for the acquisition of the ability to read (Goldberg & Lederberg, 2015;Lederberg, Schick, & Spencer, 2013;Naveka von Mentzer et al, 2013;Werfel, Douglas, & Ackal, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Given the burgeoning interest of the scientific community for the auditory-perceptual skills related to language development in children 27 28 in this prospective randomised study we sought for a "springboard", namely the acquisition of a minimum level of skills such as to expect verbal language to develop in cochlear implant patients. The first milestone is the detection of all of Ling Six Sounds, thus confirming the access to all speech frequencies.…”
Section: Discussionmentioning
confidence: 99%